CAN message unpack and pack based on simulink automatic code generation technology. Issue 1 (1st May 2022) - Yuan, Ruiteng; Xiao, Chun; Liu, Mengjie; Chen, Jing; Yu, Maochang
Abstract: Aiming at the problem of a large amount of CAN communication message data of automobile controllers and low efficiency of traditional software development, this paper proposes a method of CAN message unpack and pack based on Simulink automatic code generation technology. S-Function is used to design CAN message sending and receiving model that can import DBC files, and use RTW (real-time workshop) to realize Simulink model to automatically generate C code. This method effectively solves the unpack and pack of CAN messages, simplifies the code development process, and improves the efficiency of software development, especially when there are DBC files, which simplifies the work of sending and receiving and testing.